Molecular insights unlocking therapeutic potential for multiple myeloma and bone disease management - Tiziana Bruno; Valeria Catena; Giovanni Blandino; Maurizio Fanciulli; Silvia Di Agostino (Journal of Experimental & Clinical Cancer Research)
Abstract Multiple myeloma (MM), a hematologic malignancy characterized by the clonal expansion of plasma cells within the bone marrow, is associated with severe health complications, including osteolytic bone lesions that significantly increase the risk of fractures, leading to higher morbidity and mortality rates. One intriguing protein in this context is the RNA polymerase binding factor Che-1/AATF (Che-1), which has emerged as a potential player in the survival and proliferation of myeloma cells. Hippo pathway has been shown to be an important mediator of oncogenesis in solid tumors, especially for its role in shaping a tumor microenvironment favorable to cancer maintenance and spread. The Hippo pathway is also implicated in the pathogenesis of the osteolytic lesions that occurs in MM, since it deregulates the activities of mesenchymal populations of the bone matrix. In this commentary we wish to highlight some new molecular aspects elucidated in the paper by Bruno et al. regarding the proliferation of MM and the onset of bone lesions [Leukemia 38:877–882, 1]. A series of recent findings has revealed a crosstalk between the RNA polymerase binding factor Che-1 and the HIPPO downstream co-transcriptional factor TAZ, bringing to light new emerging molecular targets in MM to limit the development of bone lesions.